The Role of Governance Integrity in Islamic Banking; (with Emphasis on the Legal System of the Islamic Republic of Iran and Malaysia) - Ali Allahyarifard; Mahmood Ganjbakhsh (تحقیقات مالی اسلامی (پیوسته))
Realizing the basic principles of Islamic banking and implementing the basic rules and regulations of conventional banking make an absolute generality and peculiarity relationship, because Islamic banking is rooted in human nature and ethics, and its principles are not separated from those of reason and moral rules accepted by all the involved thinkers. The main question is what principles the legal system of governance fitting with Islamic banking and the goals of the Holy Sharia should include. The purpose of this article is to present the role of governance integrity in the realization of real Islamic banking, focusing on the banking system of the Islamic Republic of Iran and Malaysia. Descriptive analysis and that of the findings and concepts have been done with qualitative content analysis method through library information collection. According to the selected hypothesis, all conventional banking regulations that are to protect the rights of individuals and morals should be applied. Failure to apply prior and subsequent desirable supervision by the competent institutions mentioned in the constitution and other laws resulting in the divergence of Islamic banking governance reference laws and executive instructions, excluding some institutions from supervision by the laws approved by the governing bodies, violation of the decrees issued by the regulatory body about banking and lacking in the required expertise in Islamic banking knowledge are among the factors that prevent the implementation of true Islamic banking based on ethics in the society. It is, therefore,  suggested that governments and international organizations work out some agreements on how to apply the legal system related to supervision and compliance in common banking issues.